2020
DOI: 10.1016/j.jneuroim.2020.577198
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced encephalopathy impairs descending nociceptive pathways in rats

Abstract: Sepsis-associated encephalopathy (SAE) is a significant problem in patients with sepsis, and it is associated with a decrease in cognitive and sensitivity capability induced by systemic inflammation. SAE is implicated in reversible brain damage of several regions related to cognition, emotion, and sensation; however, it is not well established if it could affect brain regions associated with nociceptive modulation. Here were evaluated the nociceptive thresholds in rats with systemic inflammation induced by cec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(82 reference statements)
0
3
0
1
Order By: Relevance
“… 22 Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP. 23 , 24 , 25 Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research. As demonstrated in this study, septic rats showed significant cognitive deficits, including prolonged escape latency, increased escape passage, reduced frequency of cross to the platform, and enlarged neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP. 23 , 24 , 25 Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research. As demonstrated in this study, septic rats showed significant cognitive deficits, including prolonged escape latency, increased escape passage, reduced frequency of cross to the platform, and enlarged neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a common but lethal cause for multiple organ dysfunction, and SAE is the pathological change when septic damages spread to the brain, characterized by diffused brain dysfunction 22 . Based on recent studies, many brain areas, including the cortex, thalamus, hippocampus, striatum, basal ganglia, and corpus callosum could be affected by CLP 23–25 . Of note, the hippocampus region has a close association with cognitive impairment, 26 so the hippocampus tissue was selected for our research.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lateral pain system is particularly involved in the sensorydiscriminative features of pain such as the recognition of location, intensity, and nature of nociceptive stimuli (e.g., sharp or dull) [14]. It is still unknown which parts of these pain systems are involved in KS, but it has been confirmed in rodents that the periaqueductal gray, cerebellar, and cerebral cortices are involved in increased pain thresholds [11,15,16]. Since these brain areas are also impaired in people with KS, it could be that there might also be higher pain thresholds in KS [11].…”
Section: Introductionmentioning
confidence: 99%
“…O sobrenadante dos tecidos processados foi usado para quantificação de proteínas e citocinas. A concentração de proteína tecidual total foi medida pelo kit de ensaio de proteína BCA (Pierce)(Cazuza et al, 2020). Os níveis de citocinas IL1-β, IL-6 e IL-10 foram determinados usando kits ELISA apropriados (R&D Systems, Minneapolis,2.11.…”
unclassified